Mediating Effect of Audit Committee on the Connection Linking Auditor Attributes and Financial Reporting Quality: A Conceptual Framework - Saifullahi Abdullahi; Muhammad Law; Hussaini Bala; Haruna Daddau (Eurasian Journal of Management & Social Sciences)
Earlier research has shown that auditor attributes (AAT) complementary functions regarding audit committee (ACs) are complicated and go beyond a straight relationship. This research’s goal is to present a steady framework with the corresponding hypothesis and demonstrate the mediating influence of ACs on the connection involving AAT features and financial reporting quality (FRQ). To do so, we looked at the extant literature using conceptual approach on AAT, ACs, and FRQ and discovered that studies on AAT and FRQ had diverse outcomes. We also discovered there was minimal indication of non-audit service fees, industry experience, audit firm age, audit firm tangibility, responsiveness, reliability and assurance impacting FRQ. It was set up that more investigation is needed on the potential possible mediating effect of ACs on AAT and FRQ. Future research is needed to evaluate our proposed framework in greater depth empirically.